Is it safe to perform percutaneous endoscopic gastrostomy in neurological patients? - Dantas, Silvio José de Lucena; Guedes, Hugo Gonçalo; Silva, Matheus Oliveira da; Medeiros, Andressa Katarinne Cunha Siminéa; Araújo-Filho, Irami (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2014)
Purpose: Percutaneous Endoscopic Gastrostomy (PEG) has been the method of choice to provide enteral access for patients in need of nutrition for a long term. Although considered safe, the insertion of gastrostomy catheters may be associated with some complications. Objectives: The aim of this study was to analyze the immediate, technical and infectious complications of PEG in neurological patients, conducted by a reference team. Methods: We conducted a follow-up of 171 patients who underwent PEG between 2000 and 2011 at the Department of Digestive Surgery (Gastronutri) Hospital São Lucas, Natal / Brazil. Results: Of the 172 cases of PEG, there were 03 deaths until the 30th day after surgery, but none directly related to the procedure. The overall complication rate was 14.6%, among which 8.2% of patients had minor complications and only 6.4% major complications. Patients above 81 years old had lower odds of postoperative pneumonia (p = 0.004). By discriminating the time of use of a nasogastric catheter is greater or less than 06 weeks duration, it was found that the prolonged use is associated with increased incidence of postoperative pneumonia (p<0.05). Finally, if we consider malnutrition as independent correlate, malnourished patients are more likely to develop complications and pneumonia (p<0.05). Conclusion: The complication rates of PEG in our service are consistent with the literature, confirming the efficacy and safety of PEG enteral nutritional support in the neurological patients, however, not free from serious complications.